Types of valuation. (Eurasian Journal of Philology Science and Education, 2015)
This article deals with the type of valuation. There are many classifications of estimates that are based on different criteria. In modern linguistic science presents a number of estimates, the most common is the unit assessments and rational emotive. The classification assessments under the functional approach based on the principles of functionality and comparative. H.fon Wright classifies the type of evaluation and the estimated object semantics combination obscheotsenochnymi adjectives «good» and «bad». However, he points out the following types of assessments: instrumental (a good knife), technical (good driver), medical, including items such as the eyes, heart, memory, implying utilitarian fitness, useful for certain purposes: (a good plan), hedonistic (good taste ), favor (good deed).
Keywords: valuation; appreciate; general and private valuation.